До історії побудови тепловозу системи Я.М. Гаккеля - Сорочинська, О.Л. (Центр пам'яткознавства НАН України та Українського товариства охорони пам'яток історії та культури, 2009)
Кратко освещена предыстория появления отечественного тепловоза системы Я.М. Гаккеля, рассмотрена история его построения и его технические характеристики. Приведена роль в построении тепловоза отечественных ученых, конструкторов и инженеров. Prehistory of appearance of domestic diesel engine of the system of Y.M. Gakkel is briefly lighted up, history of his construction and his technical descriptions is considered. A role is resulted in the construction of diesel engine of domestic scientists, designers and engineers.